Isolation of the first IMP-4 metallo-β-lactamase producing Klebsiella pneumoniae in Tianjin, China - Li,Jing (2012)
This study shows for the first time the mechanism of carbapenem resistance of a Klebsiella pneumoniae clinical isolate TJ8 recovered from Tianjin medical university general hospital ,China. The modified Hodge test and EDTA synergy test were performed for the screening of carbapenemases and metallo-β-lactamases (MBLs), respectively. Polymerase chain reactions and DNA sequencing confirmed that the strain carried IMP-4 metallo-β-lactamase (MBL) , SHV-11 and TEM-1 β-lactamase. ClassⅠintegron was positive and gave a 3.0-kb PCR amplicon .IMP-4 was located in ClassⅠintegron 5'CS. The gene determinants were organized in the order of blaIMP-4-orfII-orfIII.In all, the results show that IMP-4 MBL production caused the TJ8 resistance to carbapenems.